2014
DOI: 10.1155/2014/362834
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels Are Associated with Expression of SLE, but Not Flare Frequency

Abstract: This study explores links between vitamin D deficiency (25(OH)D = 50 nmol/L) and serological autoimmunity (ANA > 1 : 80) and frequency of self-reported flares (SRF) in participants with clinical autoimmunity (SLE). 25(OH)D levels of 121 females were quantified and compared. The cohort consisted of 80 ACR defined SLE patients and 41 age and sex matched controls. Association analysis of log2 (25(OH)D) levels and ANA 80 positivity was undertaken via two-sample t-tests and regression models. Significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The current work reinforces the existing relationship between vitamin D deficiency and autoimmunity; 36,37 not only through the significantly higher ANA among patients with 25 OH D < 30 ng/ml, but also through the significant negative correlation between ANA and serum vitamin D levels in the studied SLE patients. This is in line with the previous assumption of Chen et al., 10 that autoantibody production may exist for many years before SLE diagnosis.…”
Section: Discussionsupporting
confidence: 85%
“…The current work reinforces the existing relationship between vitamin D deficiency and autoimmunity; 36,37 not only through the significantly higher ANA among patients with 25 OH D < 30 ng/ml, but also through the significant negative correlation between ANA and serum vitamin D levels in the studied SLE patients. This is in line with the previous assumption of Chen et al., 10 that autoantibody production may exist for many years before SLE diagnosis.…”
Section: Discussionsupporting
confidence: 85%
“…As the first analysis conducted in a large, U.S. representative sample, this adds to a suggestive literature on vitamin D deficiency and ANA based on clinical studies of lupus patients and one small sample of clinical controls (7, 15). The observed association between vitamin D deficiency and ANA was unlikely due to including individuals who receive less vitamin D due to physical impairments or illness, as the association persisted in analyses restricted to those able to perform moderate or vigorous physical activity and free of RA or thyroid problems.…”
Section: Discussionmentioning
confidence: 92%
“…ANA positivity has been associated with vitamin D deficiency in autoimmune disease patients (15-17), but little is known about vitamin D and ANA in healthy populations. One recent study examined this relationship in a small sample of clinical controls (7), but no population-based studies have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study that included 121 female patients, the investigators demonstrated that the more 25(OH)D plasma levels of patients increased, the chances for a positive ANA titer (defined as 1:80 and above) decreased. 20 Anti-dsDNA antibodies are considered extremely specific to the disease. They were found to be associated with complement levels in patients, as well as with clinical disease manifestations.…”
Section: Vitamin D Deficiency and Autoimmune Serological Markersmentioning
confidence: 99%